2011
DOI: 10.1016/j.jfms.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Lung lobe torsion associated with chylothorax in a cat

Abstract: A 10.5-year-old domestic shorthair presented with a history of progressive inappetence, lethargy and elevated respiratory rate. Clinical and diagnostic findings confirmed the presence of a chylothorax with evidence of a mass or collapsed lung within the right cranial thorax. Computed tomography, sternotomy and histopathology confirmed the presence of a right middle lung lobe torsion associated with a chylothorax. The torsion was successfully managed with surgical removal of the affected lung lobe, and the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 7 publications
0
27
0
3
Order By: Relevance
“…O quilotórax é um tipo de efusão pleural considerado incomum em gatos, poucas informações apontam a frequência destas alterações. A presença de líquido quiloso no tórax pode ocorrer secundariamente a outras afecções que afetem o sistema de drenagem ou de produção do quilo ou ainda ser caracterizado como um transtorno primário do metabolismo dos lipídeos [1,2,4,16]. No paciente descrito, as causas secundárias de quilotórax foram descartadas, tais como traumatismos, neoplasias e doenças cardíacas.…”
Section: Discussionunclassified
“…O quilotórax é um tipo de efusão pleural considerado incomum em gatos, poucas informações apontam a frequência destas alterações. A presença de líquido quiloso no tórax pode ocorrer secundariamente a outras afecções que afetem o sistema de drenagem ou de produção do quilo ou ainda ser caracterizado como um transtorno primário do metabolismo dos lipídeos [1,2,4,16]. No paciente descrito, as causas secundárias de quilotórax foram descartadas, tais como traumatismos, neoplasias e doenças cardíacas.…”
Section: Discussionunclassified
“…Causes for chylous effusions in the thoracic cavity include cardiovascular disease, neoplasia (e.g., lymphoma, thymoma, and lymphangiosarcoma), heartworm disease, diaphragmatic hernia (Kerpsack et al, 1994), lung torsion, mediastinal fungal granulomas, chronic coughing, vomiting, primary lymphedema, iatrogenic, or idiopathic Fossum et al, 1986a;Fossum et al, 1991;Fossum, 1993;Mclane and Buote, 2011;Meakin et al, 2013;Neath et al, 2000;Schuller et al, 2011;Singh and Brisson, 2010;Small et al, 2008;Waddle and Giger, 1990). Triglyceride-rich chylomicrons are derived from dietary lipids processed in the intestine and transported via lymphatics.…”
Section: Chylous Effusionsmentioning
confidence: 99%
“…[60][61][62] Torsion can occur spontaneously, 60,63 but most reported cases have an underlying respiratory disease identified or suggested, e.g., feline asthma, 64 or it may be associated with pleural effusion, including chylothorax. [60][61][62] Torsion can occur spontaneously, 60,63 but most reported cases have an underlying respiratory disease identified or suggested, e.g., feline asthma, 64 or it may be associated with pleural effusion, including chylothorax.…”
Section: Lung Lobe Torsionmentioning
confidence: 99%
“…16 It has been suggested that lesions of 0.3-0.5 cm are the absolute lower limit for radiographic identification 58 because it can be difficult to differentiate metastatic disease from other pulmonary diseases resulting in a similar radiographic pattern (e.g., pneumonia, hemorrhage, or edema). 61 Although there are only a few case reports in the literature, the prognosis is considered to be good, assuming there is no underlying effusion. Therefore, in order to ensure an accurate diagnosis is always reached, consideration should be given to undertaking ultrasound-guided fine needle aspiration of consolidated areas of lung or nodular lesions.…”
Section: Lung Lobe Torsionmentioning
confidence: 99%
See 1 more Smart Citation